Thrombotic Microangiopathy After Kidney Transplantation: An Underdiagnosed and Potentially Reversible Entity - Ávila, Ana; Gavela, Eva; Sancho, Asunción (Frontiers in Medicine, 2021)
Thrombotic microangiopathy is a rare but serious complication that affects kidney transplant recipients. It appears in 0.8-14% of transplanted patients and negatively affects graft and patient survival. It can apear as a systemic form with hemolytic microangiopathic anemia, thrombocytopenia, and renal failure, or as a localized form, with progressive renal failure, proteinuria, or arterial hypertension. Posttransplant thrombotic microangiopathy is classified as recurrent atypical hemolytic uremic syndrome or de novo thrombotic microangiopathy. De novo thrombotic microangiopathy accounts for the majority of cases. Distinguish between the two conditions could be difficult as there is an overlap between them. Complement overactivation is the cornerstone in all post-transplant thrombotic microangiopathies. It has been demonstrated in the context of organ procurement, ischemia-reperfusion phenomena, immunosuppressive drugs, antibody-mediated rejection, viral infections, and post-transplant relapse of antiphospholipid antibody syndrome. Although treatment of the causative agents is usually the first line of the treatment, this approach may not be sufficient. Plasma exchange usually resolves hematologic abnormalities but does not improve renal function. Complement blockade with eculizumab has been shown to be an effective therapy in post-transplant thrombotic microangiopathy, but at this point, it is necessary to define which patients can benefit from this therapy and when and how eculizumab should be used.